Identifying and mapping leaf nutrient based constraints for coconut productivity in Coimbatore and Tiruppur districts of Tamil Nadu state, India - Selvamani, V.; Duraisami, V.P. (Journal of Plantation Crops, 2014)
In the existing perennial plantations like coconut, leaf nutrient testing will be a promising tool to identify the existing crop nutrition related constraints and for formulating the suitable management options to improve the crop productivity. Therefore this study was conducted with the objectives of identifying the nutrient deficiency and mapping the spatial distribution of leaf based nutrient deficiency for site specific nutrient management. The study area was coconut land cover of Coimbatore and Tiruppur districts of Tamil Nadu state, India. Leaf samples and yield data were collected from 110 geo-referenced sites. Leaf samples were analysed for macro and micronutrients. The nutrient deficiency maps were developed for macro and micronutrient management. Thematic maps showed that N status was deficient in 95.99 per cent, P in 86.19 per cent, K in 1.42 per cent and Mg in 0.81 per cent area of the coconut land cover area. Ca and S were observed to be sufficient. Fe was found to be deficient in 0.64 per cent, Mn in 0.84, Zn in 0.54 per cent, Cu status in 2.62 per cent and B in 10.72 per cent of the coconut land cover area.